Transformations agricoles et agroalimentaires - Allaire, Gilles; Daviron, Benoit (éditions Quae, 2017)
This work provides a synthesis of recent research on the evolution of agriculture and food in a capitalist system. It is based on approaches not well-known in France such as international political economy and ecological economy. It studies agricultural processing in terms of ecology, history and geopolitics and traces specific aspects of agriculture and food in the 21st century. Lastly, it proposes theoretical approaches with a view to renewing the agricultural economy.